PROFESSIONAL ACCOUNTANTS’ PERCEPTIONS OF SERVANT-LEADERSHIP: CONTEXTS, ROLES AND CULTURES - Tapiwa Gande (European Scientific Journal, ESJ, 2014)
The study takes servant-leadership and attempts to find if there is an equivalent concept in management. The research design is positivist. An instrument that measures distinct leader, manager and professional role preferences is used to check the discrete operation of three contexts among a sample of members of the accountancy profession. The instrument is derived from contextualising pre-developed and pre-tested servant-leadership measuring instruments. Items from the role preference map instrument are added together with demographic details to come up with a meta-instrument adapted for the study. After validating it through pilot-testing, the instrument is applied in real-world research. The research was conducted among a sample of professional accountants in 28 countries. The research found clear and reliable servant-leadership-type behaviours exhibited across the three discreet roles and contexts of leader, manager and professional. Servant-leadership is a type of leadership that is theorised to be humanistic and spiritual rather than rational and mechanistic. Management practice on the other hand needs rationality and contains some mechanistic elements in typical management functions like coordinating and controlling. The implication is whether servant-leadership attributes can be exhibited if professional accountants contextualise themselves as leaders, managers or professionals. This approach is new in its treatment of servant-leadership in this fashion. A further original approach is the use of the accountancy profession. Additional implications relate to how professional accountants trained from a global commo syllabus by a professional body that is looking to infuse more strategic and ‘soft’ skills in their syllabi for training professional accountants.